Dynamics of soluble vascular endothelial growth factor receptors and their ligands in aqueous humour during ranibizumab for age-related macular degeneration - Ryosuke Motohashi; Hidetaka Noma; Kanako Yasuda; Osamu Kotake; Hiroshi Goto; Masahiko Shimura (BMC, 2018)
Abstract Background Intravitreal ranibizumab injection (IRI) is effective for patients with exudative age-related macular degeneration (AMD) and decreases intraocular levels of vascular endothelial growth factor (VEGF), but VEGF receptor intraocular dynamics after IRI are unclear. Therefore, we evaluated changes in the aqueous humor levels of soluble vascular endothelial growth factor receptor (sVEGFR)-1, sVEGFR-2, and their ligands for these receptors (VEGF) patients with AMD receiving IRI. Methods The subjects were 24 patients with AMD (24 eyes) who received 3 doses of IRI at monthly intervals. Aqueous humor samples were obtained when each IRI dose was given (visits 0, 1, and 2 at 4-week intervals). Then the suspension array method was employed to measure sVEGFR-1, sVEGFR-2, VEGF, and placental growth factor (PlGF) in aqueous humor samples from the 24 AMD patients and 13 cataract patients (as controls). Best corrected visual acuity (BCVA; logMAR) chart and central macular thickness (CMT; optical coherence tomography) were also assessed over time. Results At baseline, the aqueous humor levels of sVEGFR-1, sVEGFR-2, VEGF, and PlGF were significantly higher in the AMD group than in the control group. There was a significant correlation between VEGF and PlGF or between sVEGFR-1 and sVEGFR-2. BCVA and CMT both improved significantly after IRI, and the aqueous humor levels of VEGF, PlGF, and sVEGFR-1 also decreased significantly. Conclusions VEGFRs may be involved in the pathogenesis of AMD. IRI improves clinical parameters in AMD patients by suppressing intraocular levels of VEGF, PlGF, and sVEGFR-1.